(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
The thirty-second session of the General Fisheries Commission for the Mediterranean (GFCM) was attended by 23 Contracting Parties. The Commission reviewed the intersessional activities of its Scientific Advisory Committee, its Committee on Aquaculture and hold the second session of its Compliance Committee. The GFCM adopted a binding Recommendation on a Regional Scheme on Port States Measures to Combat Illegal, Unreported and Unregulated (IUU) Fishing and endorsed an International Commission for the Conservation of Atlantic Tunas (ICCAT) Recommendation on a Fishing Period for the Swordfish Fisheries...
Keywords: Fishing boats,Tàu đánh cá,Quản lý nghề cá,Fishery management